Understanding Job Portal Adoption among Users with Disabilities: A Consumer Behavior Perspective - Ervan Togatorop; Siska Jeanete Saununu; Nadya Nurlailya Ningsih (Manis: Jurnal Manajemen dan Bisnis, 2026)
This study aims to examine the influence of perceived risk, user experience, perceived security, platform credibility, and accessibility on the intention to use digital job portals among users with disabilities. The study adopts a quantitative research approach using a survey method involving 200 respondents with disabilities who have experience using digital job portal platforms such as LinkedIn, JobStreet, and Glints. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS software. The findings reveal that perceived risk has a significant negative effect on intention to use, while user experience, perceived security, platform credibility, and accessibility have significant positive effects on intention to use digital job portals. Among all variables, perceived risk emerged as the strongest predictor influencing users’ behavioral intention. The results indicate that accessible, secure, trustworthy, and user-friendly job portal platforms are more likely to encourage digital job portal adoption among users with disabilities. This study contributes to the literature on consumer behavior and digital inclusion by extending technology adoption perspectives into the context of disability-inclusive digital employment platforms.